2009
DOI: 10.2527/jas.2008-1728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antral follicle count and ovarian morphology in crossbred beef cows: Investigation of influence of stage of the estrous cycle, age, and birth weight1,2

Abstract: Depletion of the ovarian reserve is associated with reproductive senescence in mammalian females, and there is a positive relationship between the size of the ovarian reserve and the number of antral follicles on the surface of the ovary. Therefore, we conducted a series of experiments to investigate the influence of stage of the estrous cycle, age, and birth weight on antral follicle counts (AFC) in beef cows and heifers. Pairs of ovaries were collected from crossbred beef cows at slaughter (n = 72) or at nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
91
4
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 44 publications
(55 reference statements)
15
91
4
9
Order By: Relevance
“…Similar to sheep, prenatal maternal nutrition did not affect the onset of puberty in beef cattle (Martin et al 2007;Sullivan et al 2009;Mossa et al 2013), but higher offspring pregnancy rates were observed following protein supplementation in late pregnancy (Martin et al 2007) and when the AFC before breeding was high (Cushman et al 2009). In contrast, manipulation of the post-weaning diet in beef heifers did not affect AFC or overall pregnancy rate (Eborn et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 94%
See 1 more Smart Citation
“…Similar to sheep, prenatal maternal nutrition did not affect the onset of puberty in beef cattle (Martin et al 2007;Sullivan et al 2009;Mossa et al 2013), but higher offspring pregnancy rates were observed following protein supplementation in late pregnancy (Martin et al 2007) and when the AFC before breeding was high (Cushman et al 2009). In contrast, manipulation of the post-weaning diet in beef heifers did not affect AFC or overall pregnancy rate (Eborn et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 94%
“…Nevertheless, it is well established that the number of antral follicles present at all stages after birth is a direct reflection of the ovarian follicle reserve established prenatally . Thus, birthweight (as a proxy for fetal nutrient supply) was positively associated with the antral follicle count (AFC) in a large population of neonatal beef calves that died due to dystocia, and in adult heifers examined by ultrasound (Cushman et al 2009). Reduced ovarian weight and large follicle diameter at 30 months is reported following slow prenatal growth rates (Wilkins et al 2006), whereas a general reduction in all follicle types was evident following exposure to a low-then highprotein diet during the first two-thirds of gestation (Sullivan et al 2009).…”
Section: Female Offspring: Cattlementioning
confidence: 99%
“…Subsequent counts were performed twice at 35-day intervals without synchronization and in accordance with other studies (CUSHMAN et al, 2009;SILVA-SANTOS et al, 2014a), no influence of stage of estrous cycle on OAFPs was observed. However, based on consideration of ovary characteristics as well as the historical age at puberty for Girolando and Nelore breeds in the study region, heifers were considered to be prepubertal at the time of the study and were therefore not subjected to the estrus synchronization treatment administered to cows.…”
Section: Discussionmentioning
confidence: 86%
“…Marked growth of the reproductive tract observed in cattle within the first few months of age and prior to first ovulation reflects phases of increased ovarian follicle numbers and size (HONARAMOOZ et al, 2004). For beef heifers and cows, OAFPs have been correlated to birth weight and to age with an increased number of antral follicles observed until 5 years of age, following which decreasing OAFPs are seen (CUSHMAN et al, 2009). These reports are in accordance with our observation of differences in OAFPs between Nelore heifers (16.2 follicles) and cows (30.9 follicles), and between Girolando heifers (18.1 follicles) and cows (26.7 follicles), confirming an increase in OAFPs in cattle of these breeds between the ages of 12 and 60 months (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Houve efeito da doadora sobre a PIV de embriões mas não sobre a taxa de clivagem (Tabela 2), o que pode estar relacionado ao fator individual quanto à competência dos oócitos para o desenvolvimento, apesar das variações pertinentes à raça, idade e escore de condição corporal (Cushman et al, 2009). De fato, observou-se uma grande variabilidade entre as doadoras relacionada ao padrão individual de recrutamento folicular.…”
Section: Resultsunclassified